THE NAMES OF POLITICAL PARTIES IN EGYPT: A DISCOURSE ANALYSIS OF ISLAMIC POLITICAL PARTY NAMES AFTER THE ARAB SPRING 2011 - Hamdan Hamdan; Syamsul Hadi; Wening Udasmoro (CMES (Center of Middle Eastern Studies), 2025)
The Egyptian Islamic political movement gained momentum for freedom along with the 2011 Arab Spring event. The political agenda is to realise that Islamic life has the opportunity to grow again. The Egyptian Islamic political power welcomed it by establishing a political party. However, the Egyptian Law of 2011 prohibits the use of religious symbols as party identities. Therefore, the Egyptian Islamic power established it by using names from more commonly used secular concepts. This presents a distinct issue in the form of framing Islamic politics within secular discourse. This discussion attempts to examine this phenomenon by first examining the linguistic aspects of the names used by Egyptian Islamic parties. The morphological and semantic approaches are the basis of the discussion. It is concluded that the form used as the name of this party is a basic noun with an ideal meaning. The structure used is a genitive phrase as a form that gives strength to the identity carried.